Low-Density Polyethylene/Polyamide/Clay Blend Nanocomposites: Effect of Morphology of Clay on Their Photooxidation Resistance. (9th August 2017) - Dintcheva, N. Tz.; Filippone, G.; Arrigo, R.; La Mantia, F. P.
Abstract : The photooxidation behaviour of low-density polyethylene (LDPE)/polyamide (PA) blends, containing polyamide 11 (PA11) or polyamide 6 (PA6), has been investigated in the absence and presence of a small amount of commercial organomodified clay (OMMT). The polymer blends LDPE/PA11 and LDPE/PA6 at 75/25 wt./wt.%, with and without OMMT, have been prepared by a two-step procedure: extrusion and sheet formulation. The formulated complex systems have been subjected to accurate morphological analysis in order to evaluate the effect of the OMMT presence on the refinement of the blend morphology. Furthermore, the produced sheets have been subjected to arterial UVB exposure and the variations of the mechanical properties and chemical structure of all the investigated samples have been monitored as a function of the exposure time. Finally, the rate of the photodegradation of the complex systems has been related to the morphological changes of these systems upon OMMT addition.